Impact of Counselling and Health Education on Treatment Adherence and Outcomes in MDR-TB Patients (GAIMS Journal of Medical Sciences, 2026)
Background:Multidrug-resistant tuberculosis (MDR-TB) poses a major public health challenge due to prolonged treatment, high pill burden, adverse drug reactions (ADRs), and poor adherence. Non-adherence is strongly associated with unfavourable outcomes, morbidity, and mortality. Counselling and health education are critical interventions to sustain motivation, improve adherence, and enhance treatment outcomes. This study evaluates the role of counselling in MDR-TB management within the Ahmedabad Municipal Corporation (AMC).Objectives:• To assess knowledge and self-care practices related to infection control among MDR-TB patients.• To explore patients’ perceptions regarding the role of counselling in treatment adherence.• To identify challenges encountered by counsellors in delivering effective counselling.Methodology:A community-based cross-sectional study was conducted from February–October 2021 across five randomly selected TB units under AMC. A total of 115 MDR-TB patients who completed treatment between January–September 2021 were interviewed using a semi-structured proforma. In-depth interviews with five TB counsellors were also conducted. Data were collected through telephonic interviews, home visits, and open-ended discussions.Results:Of 115 patients, most acknowledged counselling as pivotal in adherence and infection control. Knowledge of self-care practices was limited, with males and less-educated patients scoring significantly lower. Counsellors identified stigma, lack of family support, and ADRs as major challenges. Nonetheless, their role was perceived as essential in sustaining adherence and facilitating treatment completion.Conclusion:Counselling and health education substantially influence adherence and outcomes in MDR-TB patients. Strengthening patient-centred counselling strategies is crucial to improve treatment success and reduce MDR-TB burden.